Observation of Electroplating in a Lithium-Metal Battery Model Using Magnetic Resonance Microscopy - Rok Peklar; Urša Mikac; Igor Serša (Molecules)
Accurate imaging methods are important for understanding electrodeposition phenomena in metal batteries. Among the suitable imaging methods for this task is magnetic resonance imaging (MRI), which is a very powerful radiological diagnostic method. In this study, MR microscopy was used to image electroplating in a lithium symmetric cell, which was used as a model for a lithium-metal battery. Lithium electrodeposition in this cell was studied by sequential 3D 1H MRI of 1 M LiPF6 in EC/DMC electrolyte under different charging conditions, which resulted in different dynamics of the amount of electroplated lithium and its structure. The acquired images depicted the electrolyte distribution, so that the images of deposited lithium that did not give a detectable signal corresponded to the negatives of these images. With this indirect MRI, phenomena such as the transition from a mossy to a dendritic structure at Sand’s time, the growth of whiskers, the growth of dendrites with arborescent structure, the formation of dead lithium, and the formation of gas due to electrolyte decomposition were observed. In addition, the effect of charge and discharge cycles on electrodeposition was also studied. It was found that it is difficult to correctly predict the occurrence of these phenomena based on charging conditions alone, as seemingly identical conditions resulted in different results.